International Trade Policies : Volume II The Uruguay Round and Beyond: Background Papers - Uimonen, Peter (World Economic and Financial Surveys; World Economic and Financial Surveys ;, 1995)
This study reviews major issues and developments in trade and their implications for the work of the IMF. Volume I, The Uruguay Round and Beyond: Principal Issues, gives an overview of the issues and developments in the world trading system. Volume II, The Uruguay Round and Beyond: Background Papers, presents detailed background papers on selected trade and trade-related issues. This study updates previous studies published under the title Issues and Development in International Trade Policy.